2012
DOI: 10.1007/s00436-012-2815-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Echinococcus species from eastern and southern Qinghai, China, based on the mitochondrial cox1 gene

Abstract: The Qinghai-Tibetan Plateau (QTP, in western China), which is the largest and highest plateau on Earth, is a highly epidemic region for Echinococcus spp. We collected 70 Echinococcus samples from humans, dogs, sheep, yaks, plateau pikas, and voles in eastern and southern Qinghai and genotyped them using the mitochondrial DNA marker cytochrome oxidase subunit I gene and maximum parsimony and Bayesian reconstruction methods. Based on the 792-bp sequence matrix, we recorded 124 variable sites, of which, 115 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…According to previous studies (Nakao et al, 2010a;Ma et al, 2012;Wang et al, 2013;Yan et al, 2013;Wang et al, 2014a), the characterization of The E. granulosus genetic network in Southeast Asia is characterized by a star-like pattern, with a predominance of the G1 genotype except in India, where the G3 genotype predominates (Sharma et al, 2013). We also found a radial network based on a common haplotype, but there were few mutation steps between the common haplotype and the others.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…According to previous studies (Nakao et al, 2010a;Ma et al, 2012;Wang et al, 2013;Yan et al, 2013;Wang et al, 2014a), the characterization of The E. granulosus genetic network in Southeast Asia is characterized by a star-like pattern, with a predominance of the G1 genotype except in India, where the G3 genotype predominates (Sharma et al, 2013). We also found a radial network based on a common haplotype, but there were few mutation steps between the common haplotype and the others.…”
Section: Discussionmentioning
confidence: 69%
“…A number of mitochondrial and nuclear fragments have been used as markers to investigate the genotypes, or the genetic structures, of E. granulosus in southwestern China, including cox1, nad1, nad2, cytb, atp6, 12S rRNA, and 16S rRNA (Ma et al, 2008;Nakao et al, 2010a;Ma et al, 2012;Wang et al, 2013;Yan et al, 2013;Wang et al, 2014a;Zhong et al, 2014). However, markers of different lengths are not appropriate for the comparison of genetic structures in different regions, and gene fragments may not be representative because every fragment on a gene is unique in terms of its conservation characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…29 Globally, many studies identified the G1 genotype as the most common or the only genotype causing human CE, whereas the G6 genotype has indicated no or low infectivity to humans. 55,[57][58][59][60][61] However, the G1 and G6 genotypes of E. granulosus genotypes are most commonly associated with human infection worldwide and in Iran. Table 4 summarizes the identification of the G6 genotype in humans across the world.…”
Section: Discussionmentioning
confidence: 99%
“…E. shiquicus infections have not been detected in humans (Xiao et al, 2005(Xiao et al, , 2006. Ma et al (2012) collected 70 Echinococcus samples (larval and adult) from sheep, yak, pikas, voles, dogs, and humans in the Qinghai-Tibet Plateau. The majority of Echinococcus samples were identified as E. multilocularis and E. granulosus s.l.…”
Section: Echinococcus Multilocularis (Leuckart 1863)mentioning
confidence: 99%